Two-dimensional ultrasound imaging of the diaphragm: Quantitative values in normal subjects - Boon, Andrea J.; Harper, Caitlin J.; Ghahfarokhi, Leili Shahgholi; Strommen, Jeffrey A.; Watson, James C.; Sorenson, Eric J. (Muscle & nerve, 2013)
Introduction: Real time ultrasound imaging of the diaphragm is an under‐used tool in the evaluation of patients with unexplained dyspnea or respiratory failure. Methods: We measured diaphragm thickness and the change in thickness that occurs with maximal inspiration in 150 normal subjects, with results stratified for age, gender, body mass index, and smoking history. Results: The lower limit of normal diaphragm thickness at end expiration or functional residual capacity is 0.15 cm, and an increase of at least 20% in diaphragm thickness from functional residual capacity to total lung capacity is normal. A side to side difference in thickness at end expiration of > 0.33 cm is abnormal. Diaphragm thickness and contractility are minimally affected by age, gender, body habitus, or smoking history. Conclusions: This study confirms previous findings in much smaller groups of normal controls for quantitative ultrasound of the diaphragm and provides data that can be applied widely to the general population. Muscle Nerve 47: 884–889, 2013